2020
DOI: 10.32003/igge.736283
|View full text |Cite
|
Sign up to set email alerts
|

Using the Word Association Test in Geography Courses as a Diagnostic Tool: Example of Plants

Abstract: Bu araştırma ile ortaöğretim öğrencilerinin Coğrafya dersi kapsamında bitkiler konusuyla ilgili olarak bilişsel yapılarının belirlenmesinde alternatif bir ölçme değerlendirme aracı olan Kelime İlişkilendirme Testinin (KİT) tanı aracı olarak kullanılması amaçlanmıştır. Araştırmanın katılımcılarını, 2018-2019 eğitim ve öğretim yılında Konya'da bir ortaöğretim kurumunda öğrenim gören 10. sınıf öğrencileri arasından amaçlı örnekleme yöntemlerinden ölçüt örnekleme yöntemi kullanılarak belirlenmiş 35 öğrenci oluştur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…In this test, each value was written 5 times in a vertical line by allocating 2 minutes for each value. In the relevant literature, some studies have reported 10 responses from the students on the word association test (Buldur et al, 2020;Kaya and Akış, 2015) while some others have noted 5 responses (Demirkaya et al, 2020;Ercan et al, 2010). Likewise, the time given for answering the items have been noted as 30, 60 and 75 seconds (Aladağ et al, 2018;Atabek Yiğit, 2015;Bahar et al, 1999;Bozyiğit & Kaya, 2017;Gussarsky & Gorodetsky, 1988;Kaya & Akış, 2015;Kaya & Aladağ, 2018;Nakiboğlu, 2008;Preece, 1978).…”
Section: Data Collection Toolmentioning
confidence: 99%
“…In this test, each value was written 5 times in a vertical line by allocating 2 minutes for each value. In the relevant literature, some studies have reported 10 responses from the students on the word association test (Buldur et al, 2020;Kaya and Akış, 2015) while some others have noted 5 responses (Demirkaya et al, 2020;Ercan et al, 2010). Likewise, the time given for answering the items have been noted as 30, 60 and 75 seconds (Aladağ et al, 2018;Atabek Yiğit, 2015;Bahar et al, 1999;Bozyiğit & Kaya, 2017;Gussarsky & Gorodetsky, 1988;Kaya & Akış, 2015;Kaya & Aladağ, 2018;Nakiboğlu, 2008;Preece, 1978).…”
Section: Data Collection Toolmentioning
confidence: 99%